FACTORS INFLUENCING CONSUMER PURCHASE INTENTION TOWARDS IMPORTED BEDDING BRANDS - Praditbatuga, Piyathida; Thirakomen, Nichapa (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
The objective of this study was to determine the factors that influence consumer purchase intention towards imported bedding brands in Thailand, based on the Theory of Reasoned Action model (Fishbein & Ajzen, 1975). Data was collected via questionnaires applying the convenience sampling technique to select respondents. One hundred and eighty sets of questionnaires were distributed to customers in department stores in Bangkok once the reliability and validity of the instrument were established. A total of 140 sets out of the 180 sets were completed and returned. The independent variables were the attitude towards products and subjective norms, and the dependent variable was purchase intention. Frequency and percentage were used to analyze the demographic profile. Mean and the standard deviation was used to analyze respondents’ perception of each variable. Hypotheses were tested with Multiple Linear Regression Analysis. The results from the Multiple Linear Regression Analysis demonstrated that attitude towards the product and subjective norm both significantly influence consumer purchase intention. However, attitude towards the product (Beta = 0.618) had more influence on purchase intention than the subjective norm (Beta = 0.151).